Should COVID-19 be branded to Viral Thrombotic Fever? - Costa Filho, R. C. (2021)
Hospital Pró-Cardíaco. Founder and coordinator of Department of Critical Care. Americas Medical Services. United Health Group. Rio de Janeiro, RJ, Brasil.